Originally Posted by

**HallsofIvy** You have now written "x^3 = 7x^2 + 12x = 0", in your original post, "x^3 + 7x^2 = 12x = 0", in post number 6, and The Chaz wrote "x^3 + 7x^2 + 12x = 0" in post number 7. which is it?

If it is, indeed, x^3 + 7x^2 + 12x = x(x^2+ 7x+ 12)= x(x+ 3)(x+ 4)= 0, then the "zero property" gives you all three roots: the product of x(x+ 3)(x+ 4) is 0 only if at least one of the three factors is 0: x= 0, or x+ 3= 0, or x+ 4= 0.

You also seem to be very confused about exactly what you are trying to do. You say "It seems that I have only found two solutions though? (x+3) and (x+4)". Those are NOT "solutions". The three solutions you want are the three **numbers** that satisfy the equation. If x+ 3= 0 what is x? If x+ 4= 0, what is x? Now what was the third factor, above?